APLIKASI SISTEM INFORMASI PENJUALAN OBAT DI APOTEK DENGAN MENGGUNAKAN METODE VISUAL BASIC 6 - Onny Purnamayudhia (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract The effort management in the field of pharmacy, especially in medicine sales, needed a sales information database. This application system use database system design in form of flow chart document, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD) and Context diagram. Application of this database system using programming language as a Microsoft Visual basic 6. Medicine sales information system in this pharmacy displayed forms of table and flow charts to determine overall reports of sales. The connection of sales report, there are inventories information systems of raw material and finished goods (medicine) which are an integral part of sales information. Information of Inventories include data input of raw material and medicine inventory report divided follow in master and sort of raw material and medicine account. Source of inventori record consist of : Purchase order document, List of supplier and customer identity, Goods receipt report, sales report. The purpose in this research are to analyze and design to medicine sales information systems in pharmacy and applicated in integrated systems which give useful to board of management for decision making process exactly in relation of consumer demand need.